Clinical application of regional and intermittent hepatic inflow occlusion in laparoscopic hepatectomy - Shi, Longqing; Luo, Baoyang; Yang, Yong; Miao, Yurong; Li, Xin; Sun, Donglin; Zhu, Qiang (Frontiers in Oncology, 2022)
Aim: To investigate the advantages and disadvantages of regional and intermittent hepatic inflow occlusion in laparoscopic hepatectomy. Methods: The clinical data of 180 patients who underwent laparoscopic liver surgery in Taizhou People's Hospital from 2015 to 2021 were analyzed retrospectively. The patients were divided into the regional occlusion group (n = 74) and Pringle’s maneuver occlusion group (n = 106) according to the technique used in the intraoperative hepatic inflow occlusion. The pre- and intra-operative indicators, postoperative recovery indicators, and complications of the two groups were compared. Results: There were no significant differences (p>0.05) between the groups in terms of sex, age, preoperative alanine aminotransferase (ALT), preoperative aspartate aminotransferase (AST), preoperative albumin, alpha-fetoprotein, liver cirrhosis, hepatitis B, tumor location, gas embolism, intraoperative blood transfusion, postoperative albumin, postoperative total bilirubin (TBIL), postoperative hospital stays, and complications. The preoperative TBIL and operation time were higher in the regional occlusion group than in the Pringle’s maneuver occlusion group, while the amount of intraoperative bleeding, postoperative ALT, and AST in the regional occlusion group were significantly lower than those in the Pringle’s maneuver occlusion group (p<0.05). Conclusion: The two occlusion techniques are equally safe and effective, but regional hepatic inflow occlusion is more advantageous in operation continuity, intraoperative bleeding, and postoperative liver function recovery. The long duration and high precision of the regional blood flow occlusion technique demands a more experienced physician with a higher level of operation; therefore, it can be performed by experienced laparoscopic liver surgeons.